The association between neighborhood residential rehabilitation and injection drug use in Baltimore, Maryland, 2000-2011 - Linton, Sabriya L. (Health Place, 2014)
This study utilized multilevel cross-classified models to longitudinally assess the association between neighborhood residential rehabilitation and injection drug use. We also assessed whether relocating between neighborhoods of varying levels of residential rehabilitation was associated with injection drug use. Residential rehabilitation was categorized into three groups (e.g. low, moderate, high), and lagged one visit to ensure temporality. After adjusting for neighborhood and individual-level factors, residence in a neighborhood with moderate residential rehabilitation was associated with a 23% reduction in injection drug use [AOR=0.77; 95% CI (0.67,0.87)]; residence in a neighborhood with high residential rehabilitation was associated with a 26% reduction in injection drug use [AOR=0.74; 95% CI (0.61,0.91)]. Continuous residence within neighborhoods with moderate/high rehabilitation, and relocating to neighborhoods with moderate/high rehabilitation, were associated with a lower likelihood of injection drug use. Additional studies are needed to understand the mechanisms behind these relationships.